Foresight partnership forum: Forum report - CGIAR Initiative on Foresight; Wiebe, Keith D.; Gotor, Elisabetta (CGIAR, 2023)
Background | The challenges facing food, land, and water systems are numerous and complex. In addressing these interlinked challenges, the choices facing governments and their development partners have also become increasingly complicated. Synergies are possible, but trade-offs are often unavoidable. Decision-makers need better evidence to help them choose actions that minimize trade-offs and advance progress towards collective goals. The CGIAR Foresight Initiative aims to inform these choices and enhance decision-making about the future by combining advanced analytics and close engagement with national, regional, and global partners. The Initiative forms part of CGIAR’s new research portfolio, delivering science and innovation to transform food, land, and water systems in a climate crisis. Objectives | The Foresight Partnership Forum brought together key partners from across Sub-Saharan Africa to explore challenges facing food, land, and water systems at national, regional, and global scales; identify opportunities to share and strengthen capacity for foresight; and examine ways to use foresight tools and analysis to inform policy making. The Forum on 24-25 January was followed by a training session on country development and policy modeling for partners on 26-27 January.